KARTINI FROM ALOR: EMERGING THE DISCOURSE OF TEACHER'S PROFESSIONAL IDENTITY IN KICK ANDY AND KUMPARAN - Raisa Rakhmania; Rustono Farady Marta; Hana Panggabean; Changsong Wang (al-Balagh : Jurnal Dakwah dan Komunikasi, 2023)
Education is commonly perceived as the process of having systematic instruction from educators for better living quality, and sometimes, it means higher lifetime earnings. Teachers play an important role in educating the next generation. The Indonesian talk show “Kick Andy” and the news portal “Kumparan” released on Youtube, show a message on education. These programs narrate the story of an early-childhood-education teacher from a remote area in Nusa Tenggara Timur. Both programs illustrate a woman’s struggle to obtain an education opportunity and provide access to education among the children in her village. The data was collected with an interview method. Data were available on television and online media platform. This study employs a framework by Sara Mills’s critical discourse in a combination of the teacher’s professional development theory to rectify how mass media portrays a female teacher who lives in a marginal area. Based on the collected data in Ibusm State, on the one hand, this study finds that the media still depicts women as submissive and oppressed figures who should serve the family and country. On the other hand, it is found that women are empowered to rise from adversity, which is also reinforced by a strong teacher’s professional identity in a teacher’s self.